Abdominal Wall Clear Cell Carcinoma: Case Report of a Rare Event with Potential Diagnostic Difficulties - Maria del Mar Rivera Rolon; Dyron Allen; Gwyn Richardson; Cecilia Clement (Hindawi Limited, 2019)
Clear cell carcinoma (CCC) is a well-known aggressive histological type of carcinoma, predominantly seen in ovary and endometrium. However, CCC arising in abdominal wall is a very rare event. We report a case of a 48-year-old woman with an abdominal wall mass at her cesarean section (c-section) scar, which increased in size and became painful in the last months. Radiology revealed a 7 cm mass in the right inferior rectus muscle sheath, suggestive of endometriosis. An irregular, firm mass was resected, densely adherent to the rectus muscle and pubic bone. Frozen section revealed a multicystic lesion with minimal cytologic atypia, and a benign cystic neoplasm was favored. However, permanent sections showed marked nuclear atypia, hobnail morphology, and areas of infiltrative growth within fibrous stroma. No benign endometrial glands were found, although fibrosis and hemorrhage were present. Napsin-A, racemase, and PAX-8 were positive, consistent with CCC, likely arising within a c-section endometriosis focus. Although CCC usually presents with moderate to marked nuclear atypia, it can be mild and, especially in cases with a predominant cystic pattern, create diagnostic difficulties. An endometriosis-associated malignancy should be considered in the differential with any enlarging nodule or increasing pain within an abdominal wall scar.